PSXIII-11 Altering length of the presynchronization period in a long-term progestin-based estrus synchronization protocol for timed artificial insemination of beef heifers. (5th December 2019) - Knickmeyer, Emma R; Thomas, Jordan M; Locke, James William C; Bonacker, Rachael C; Ciernia, Lauren; Ketchum, Jaclyn N; Ellersieck, Mark R; Poock, Scott E; Smith, Michael F; Patterson, David J
Abstract: An experiment was designed to evaluate the effect of extending the presynchronization period in a progestin-based estrus synchronization protocol. Heifers were assigned to an 18 d or 14 d CIDR ® treatment (1.38 g progesterone), with prostaglandin F2α (PG; 250 mg im) administered 16 d after CIDR ® removal (Day 34). Heifers at two locations (location one, n = 193; location two, n = 649) were assigned to treatment based on reproductive tract score (RTS; Scale 1–5) and weight. Estrus detection aids (Estrotect ® ) were applied at PG and split-time artificial insemination (STAI) was performed based on estrus expression at 66 h. Heifers that expressed estrus at 66 h were inseminated and heifers that did not express estrus were inseminated at 90 h. Only heifers that failed to express estrus by 90 h received gonadotropin-releasing hormone (GnRH; 100 µg im) at AI. At location one, blood samples were collected at PG and AI (66 h or 90 h) from all heifers to determine E2 concentrations, and transrectal ovarian ultrasound was performed to detail ovarian structures on a subset of heifers (n = 73) at both time points. The proportion of heifers expressing estrus by 66 h (60%) or in total by 90 h (84%) after PG did not differ between treatments. Pregnancy rate to STAI did not differ between treatments (P = 0.3; 52%, 14 d CIDR ® -PG; 50%, 18 d CIDR ® -PG), or at the end of the 60 d breeding season (P = 0.2). There were no differences between treatments in mean diameter of the dominant follicle at PG (P = 0.6) or STAI (P = 0.3), nor were any differences observed between treatments in E2 concentrations at PG (P = 0.8) or STAI (P = 0.6). These data suggest that CIDR ® treatment can be extended from 14 to 18 d, providing flexibility in scheduling without compromising reproductive outcomes.